Blast responses of concrete beams reinforced with steel-GFRP composite bars. (December 2019) - Liu, Sanfeng; Zhou, Yinzhi; Zheng, Qing; Zhou, Jiannan; Jin, Fengnian; Fan, Hualin
Abstract: Steel-GFRP (glass fiber reinforced polymer) composite bars (SGCBs) have advantages in corrosion-resistance and high load-bearing capacity endowed by GFRP, as well as ductility inherited from steel bars. They can be used as reinforcements in concrete protective structures. Two types of composite-bar reinforced concrete beams (CRCBs) were designed and casted. Explosion experiments reveal that cracking and spalling are the main damage patterns of the CRCBs. Composite bars reduce the plastic deformation and the residual deflection compared with the steel-bar reinforced concrete beams (SRCBs). Anti-blast ability is evaluated by quasi-static four-point-bending experiment on exploded beams. Intact CRCBs have three typical deformation stages, including elastic, elastoplastic and post-plastic deformations, and fail when the mid-span flexural crack almost runs through the beam. GFRP bars make the CRCB have much greater load capacity than the SRCB. Exploded beams have similar deformation and failure styles with the unexploded beam and even have greater load capacity than the unexploded SRCB. Having both high load capacity and excellent ductility, the SGCBs have advantages over steel bars in protective structures in some cases.